Selection of Early Cauliflower Variety for Income Generation - Bhattarai, Dhruba Raj; Pardhan, Navin Gopal; Chalise, Basanta; Piya, Sarmila (Nepal Journal of Science and Technology, 2015)
An early cauliflower genotype HRDCAU005 was developed from a mix population of Kathmandu Local variety by mess selection at Horticulture Research Division, Lalitpur, Nepal. The developed genotype was 20 days earlier than the Kathmandu Local. The performance of this genotype was evaluated in 2012 and 2013 at different locations; Lalitpur, Kavre, Dailekh and Pakhribas. The experiment was laid out in a randomize complete block design with five replications in all the years and locations. In farmers’ field conditions, the highest fresh curd yield was recorded in Kathmandu Local ( 41.9 t/ha) followed by HRDCAU005 ( 29.72 t/ha) and White Flash (28.41 t/ha). Maximum attack of diamond back moth (DMB) was found in White Flash, one of the check variety, whereas the least diamond back moth attack was observed in the genotype HRDCAU005. Despite relatively low yield than Kathmandu Local variety, farmers preffered HRDCAU005 for its earliness, attractive colour, marketable curd size, good cooking quality, better taste and good market price of fresh curd. DOI: http://dx.doi.org/10.3126/njst.v15i1.12003 Nepal Journal of Science and Technology Vol. 15, No.1 (2014) 1-6